Surgical implantation of temperature‐sensitive transmitters and data‐loggers to record body temperature in koalas (Phascolarctos cinereus). Issue 1 (18th January 2016) - Adam, D; Johnston, SD; Beard, L; Nicholson, V; Lisle, A; Gaughan, J; Larkin, R; Theilemann, P; Mckinnon, A; Ellis, W
Abstract : Background: Under predicted climate change scenarios, koala distribution in Australia is expected to be adversely affected. Recent studies have attempted to identify suitable habitat, based on models of bioclimatic regions, but to more accurately reflect the thermal tolerance and behavioural adaptations of the various regional populations, the koala's response to periods of heat stress will need to be investigated at the individual animal level. Objective: To explore the safety and suitability of temperature‐sensitive intra‐abdominal implants for monitoring core body temperature in the koala. Methods: A temperature‐sensitive radio transmitter and thermal iButton data‐logger, waxed together as a package, were surgically implanted into the abdominal cavity of four captive koalas. In one animal the implant was tethered and in the other three, it was left free‐floating. Results: After 3 months, the implants were removed and all four koalas recovered without complications. The tethering of the package in the one koala resulted in minor inflammation and adhesion, so this practice was subsequently abandoned. The free‐floating deployments were complication‐free and revealed a diurnal body temperature rhythm, with daily ranges of 0.4–2.8°C. The minimum recorded body temperature was 34.2°C and the maximum was 37.7°C. The difference in the readings obtained from the transmitters and iButtons never exceeded 0.3°C. Conclusions: The suitability of the surgical approach was confirmed, from both the animal welfare and data collection points of view.